2006
DOI: 10.1016/s1808-8694(15)31015-6
|View full text |Cite
|
Sign up to set email alerts
|

Topical mitomycin C effect on swine vocal folds healing

Abstract: topical application of MTC after the exeresis of a mucous fragment of vocal fold with CO2 laser in swine significantly decreased total collagen deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This result agrees with the other studies findings 11 , showing lower collagen's deposition when using mitomycin.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result agrees with the other studies findings 11 , showing lower collagen's deposition when using mitomycin.…”
Section: Discussionsupporting
confidence: 94%
“…Camargo et al 11 , when studying a pigs' group with laser exeresis and later application of mitomycin, had a mean area of 2648.03 µm 2 concerning to the vocal fold's total collagen in the control group, while the experimental group's total collagen was 2200.30 µm 2 (P = 0.0043), demonstrating a significant difference when using mitomycin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For modulation of wound‐healing processes and for attenuating scarring, one of the possible solutions described in the scientific literature is the application of antifibrotic drugs on primary lesions. For this purpose, various antifibrotic pharmaceutical agents such as corticosteroids, 5‐fluorouracil, carnitine, and mitomycin‐C (MMC) have already been employed either alone in short‐term local surface applications or as at our clinic in combination with preceding laser excision of cicatricle tissue in laryngotracheal stenosis treatment. Although MMC is a traditional chemotherapeutic drug, isolated from Streptomyces sp ., it has also been regarded as a compound with high potential to prevent tissue fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Authors suggested that mitomycin C may delay but does not necessarily prevent the recurrence of stenosis. Animal studies including canines, [20][21][22][23][24] rabbits, 25 and swine 26,27 also showed the improvement of airway wound healing after mitomycin C application. Specific to the management of vocal fold scarring, topical application of mitomycin C has been shown to lead to (1) reduced anterior glottic web formation, (2) decreased total collagen deposition, (3) improved cricoarytenoid joint mobility, and (4) decreased granulation tissue development.…”
Section: Introductionmentioning
confidence: 99%